Innovation of Physics Learning Media Based on Web Enhanced Course at SMK N 5 Konawe Selatan - Marwana Marwana; Nurjannah S. G; Wa Ode Fifianti; Rosliana Eso (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
Enhanced Web Course m erupakan Web-logs that me benefit k an internet in presenting the material of learning. The use of instructional media especially in learning basic physics is still very low , this is based on questionnaire data and interviews with Physics subject teachers at SMK N 5 SELAW KONAWE . The use of Web Enhanced Course learning media enables interactive communication between teachers and students , both individually and in groups, and can be an alternative learning online. The purpose of this paper is to utilize the Web Enhanced Course as a learning medium that makes it easy to learn about Basic Physics. Web Enhanced Course learning media that have been made, validated by instructional design experts, instructional media experts, and website designer experts and obtained a value with the criteria of